Peningkatan Kapasitas Masyarakat dalam Penyelenggaraan Event Olahraga Antar Kampung yang Berbasis Partisipasi dan Tata Kelola Profesional dari Perspektif Hukum - Fakultas Hukum Universitas Negeri Surabaya; Dita Perwitasari; Masda Agatha Sari; Kharizha Krishnandya; Bagus Rahmanda (Jurnal Darma Loka, 2025)
Organizing local sports events, such as inter-village tournaments, carries significant potential to stimulate both social and economic growth. However, this potential is often hindered by limited knowledge of legal requirements and inadequate event management. Poorly managed activities may expose organizers to legal challenges, including permit violations, liability for participant or spectator injuries, and disputes over sponsorship arrangements. This community-driven initiative seeks to strengthen the legal and managerial competencies of local groups in hosting participatory sports events. The program emphasizes structured training and mentorship, focusing on licensing procedures, drafting agreements with sponsors and third parties, and managing legal risks effectively. Through this effort, communities are expected to develop the capacity to manage events in a professional, transparent, and accountable manner. In the long run, inter-village competitions can serve as safe and sustainable platforms that make a tangible contribution to community well-being. The outcomes indicate a substantial improvement in community awareness regarding the legal and administrative aspects of event organization.